2003
DOI: 10.1007/s00268-003-7106-5
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Form and Function during Management of Cancer of the Larynx and Hypopharynx

Abstract: The treatment of laryngeal and hypopharyngeal cancer has seen notable changes during the twentieth century. Intensive surgical research has allowed laryngologists to deal with almost any local extension and to propose an appropriate surgical procedure for each case. This surgery is able to control the disease in most patients locally but is limited in its indications (resectable diseases and operable patients). On the other hand, radiotherapy has been impressively improved (dosimetry, definition of target volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…1,2 This strategy has led to controversial issues concerning the role of lymph node dissection following radiotherapy or chemoradiation for patients with advanced regional disease at initial diagnosis. Selective neck dissection (SND) was reported as suitable after chemoradiation in patients with advanced regional disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 This strategy has led to controversial issues concerning the role of lymph node dissection following radiotherapy or chemoradiation for patients with advanced regional disease at initial diagnosis. Selective neck dissection (SND) was reported as suitable after chemoradiation in patients with advanced regional disease.…”
Section: Introductionmentioning
confidence: 99%
“…Keywords: head and neck cancer; lymph nodes; neck dissection; squamous cell carcinoma Recent nonsurgical approaches for advanced head and neck squamous cell carcinoma (HNSCC), through the use of chemotherapy and radiotherapy, have demonstrated that organ preservation was feasible without compromising disease-free survival and overall survival. 1,2 This strategy has led to controversial issues concerning the role of lymph node dissection following radiotherapy or chemoradiation for patients with advanced regional disease at initial diagnosis. Residual neck mass may be present in as many as 30% to 50% of patients after completion of chemoradiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Organ preservation protocols with a combination of chemoradiation (CRT) are currently accepted as the first‐line therapeutic modality for patients with locally advanced hypopharyngeal squamous cell carcinoma (SCC) 1. The management of recurrences after such treatments remains challenging, particularly because of postradiation inflammation and fibrosis 2–6.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 With rehabilitation, total laryngectomy usually results in acceptable speech and swallowing; however, the stigma associated with a tracheostoma is a significant concern to patients and their families. 3,4 Alternatively, SCPL is associated with high local control rates and allows preservation of speech and swallowing without a permanent tracheostomy.…”
mentioning
confidence: 99%